Proyecto asociativo para los pequeños productores del follaje ornamental (Ruscus Hypophyllum) de las parroquias de Guayllabamba, Yaruquí y Checa hacia el mejoramiento de la comercialización y distribución en las florícolas del sector de Cayambe - Campaña Machuca, Ruth Maribel (2014)
The production, marketing and exporting Ecuadorian floriculture is the most dynamic exportable activity and rise in the last years, as export Gaps stands, they are made and decorated with green foliage, floriculture line that has not been the 100% exploited, which is why this proyect seeks the strategy of small producers of ornamental foliage (Ruscus Hypophyllum) parish of Guayllabamba, Yaruquí and Checa alliance because, at the time known production and domestic marketing of these farms, empirically-traditional way and with little organization, with the aim of seeking a common good for getting involved reducing costs by working with a series production and standardized prices by creating a partnership with a potential market floriculture in Cayambe demanding 3.312 million stems per year.